Degradable medicinal plastic bottle and preparation method thereof
By combining polylactic acid, biodegradable elastomer, compound plasticizer and photosensitizer, melt blend blow molding, combined with modified titanium dioxide and Ag3PO4, a degradable drug with excellent mechanical properties and moderate degradation properties is prepared. The use of plastic bottles solves the problems of difficult degradation and insufficient mechanical properties of existing medicinal plastic bottles, and achieves environmentally friendly and safe medicinal packaging materials.
Patent Information
- Application Number
- CN202411817725.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-12-11
AI Technical Summary
Existing pharmaceutical plastic bottles are difficult to degrade, resulting in environmental pollution, and the mechanical properties of the degradable materials are insufficient and cannot be applied to pharmaceutical plastic bottles.
Using a combination of polylactic acid, biodegradable elastomer, compound plasticizer, nucleating agent and photosensitizer, melt blending and blow molding is carried out through a twin-screw extruder to prepare a modified mechanical properties and degradable properties. Medicinal plastic bottles, using modified titanium dioxide and Ag3PO4 to improve photocatalytic efficiency and antibacterial properties.
It significantly improves the mechanical properties and toughness of polylactic acid, improves photocatalytic efficiency, controls the degradation rate, and maintains the cleanliness and hygiene of drugs through antibacterial properties, solving the shortcomings of physical properties, photocatalytic efficiency and antibacterial properties in the prior art. question.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic materials, in particular to a degradable medicinal plastic bottle and a preparation method thereof. Background Art
[0002] In the field of pharmaceutical packaging, plastic bottles are widely used because of their light weight, durability, and ease of processing and transportation. With the general improvement of global environmental awareness, the use of degradable materials has become an important trend in the packaging industry. However, most of the existing pharmaceutical plastic bottles have failed to follow this trend in terms of material selection and still use a large amount of non-degradable materials, which not only limits the environmental performance of pharmaceutical plastic bottles, but also limits their competitiveness in the future market.
[0003] In the Chinese invention patent CN111216338B, a processing method for pharmaceutical plastic bottles is described in detail. This method not only focuses on the production efficiency and cost control of plastic bottles, but also improves the scope of application and flexibility of plastic bottles through technological innovation. However, although pharmaceutical plastic bottles play an important role in protecting drugs from external environmental interference, ensuring drug stability and extending the shelf life of drugs, existing pharmaceutical plastic bottles still have some significant problems. For example, traditional pharmaceutical plastic bottles are mainly made of non-degradable materials such as polyethylene (PE), polypropylene (PP) or PET. These plastic bottles are difficult to decompose naturally after being discarded, causing long-term pollution to the environment; existing degradable materials have mechanical property defects, which make them unable to be used in pharmaceutical plastic bottles. Summary of the invention
[0004] 1. Technical issues to be resolved In view of the deficiencies in the prior art, the present invention provides a degradable medicinal plastic bottle and a preparation method thereof, which solves the problem that the existing medicinal plastic bottles are difficult to degrade.
[0005] (II) Technical solution To achieve the above objectives, in the first aspect, the present application provides a degradable medicinal plastic bottle and a preparation method thereof, which adopts the following technical solutions: In a first aspect, the present invention provides a degradable medicinal plastic bottle, the raw material components include polylactic acid, a biodegradable elastomer, a compound plasticizer, a nucleating agent, and a photosensitizer, wherein the mass ratio of polylactic acid, biodegradable elastomer, compound plasticizer, nucleating agent, and photosensitizer is 100: (15-20): (2-4): (2-4): (1-3); The biodegradable elastomer is obtained by mixing polyhydroxybutyrate, polycaprolactone, polybutylene succinate and the like in a weight ratio; the compound plasticizer is obtained by mixing a bio-based polycarboxylic acid plasticizer, a cellulose-grafted polycaprolactone derivative, modified castor oil, and acetyl tributyl citrate; the nucleating agent is one of a polylactic acid stereocomplex and TMC-200; the photosensitizer is modified titanium dioxide; The raw material components are mixed evenly and then added into a twin-screw extruder, and a degradable medicinal plastic bottle is prepared through melt blending and blow molding.
[0006] Preferably, the polylactic acid is a mixture of poly L-lactic acid and poly D-lactic acid, and the polylactic acid has a glass transition temperature of 60°C, a melting point of 180°C, a tensile strength of 50-65MPa, an elastic modulus of 2000-3500MPa, an elongation of 6%-10%, and a relative density of 1.24g / cm 3 .
[0007] Preferably, the polylactic acid has a glass transition temperature of 60°C, a melting point of 180°C, a tensile strength of 50-65MPa, an elastic modulus of 2000-3500MPa, a flexural strength of about 100MPa, a flexural modulus of 3000-4000Mpa, and a relative density of 1.24g / cm 3 Preferably, the modified titanium dioxide is obtained by: Step S11, weigh a certain amount of loose dry kapok, and soak it in an absolute ethanol solution of TBOT at room temperature, let it stand for 24 hours, then take it out and place it in the air for hydrolysis for 2 hours; Step S12: After the hydrolysis is completed, the kapok is placed in a drying furnace and dried and calcined at 50° C., and the tubular TiO2 is collected for later use; Step S13, under magnetic stirring, add 0.1 g of AgNO3 to 50 mL of an aqueous solution containing 0.5 g of PVP, stir for 30 min, disperse 200 mg of tubular TiO2 in the solution, stir again for 30 min, slowly drop 5 mL of 0.1 mol NaHPO4 into the solution, and let stand for 4 h after ultrasonic stirring; Step S14, collecting the precipitate by centrifugation, washing twice with deionized water and anhydrous ethanol, and then placing the sample in a drying oven and drying it at 50° C. for 6 h to obtain a 1:2 Ag3PO4 / TiO2 composite material; Step S15, surface modification of the collected Ag3PO4 / TiO2 composite material is performed by using a silane coupling agent to improve the stability of the Ag3PO4 / TiO2 composite material and improve its light absorption performance and photocatalytic activity; Step S16, drying in a drying oven at 60°C for 24 hours. In order to improve the crystallinity of the Ag3PO4 / TiO2 composite material nanoparticles, the Ag3PO4 / TiO2 composite material is annealed in a muffle furnace at 350°C for 2 hours to obtain modified titanium dioxide.
[0008] The explanation shows that the combination of Ag3PO4 and titanium dioxide can effectively improve the light absorption performance of plastic bottles and accelerate the degradation rate; after ultrasonic stirring, the tubular titanium dioxide breaks into tile-like pieces, and still has a large surface area after mixing with Ag3PO4; when the Ag3PO4 content is too high, the degradation rate slows down because it covers the active points of titanium dioxide. After mixing with other raw materials, Ag3PO4 particles act as "fillers", which can increase the density and hardness of plastics, improve impact resistance and wear resistance, and at the same time interact with plastic molecular chains to form physical cross-linking points, further enhancing mechanical properties and hardness.
[0009] Preferably, the composite plasticizer is obtained by mixing a bio-based polycarboxylic acid plasticizer, a cellulose-grafted polycaprolactone derivative, modified castor oil, and acetyl tributyl citrate in a ratio of 2:2:1:1, calculated by mass fraction.
[0010] Preferably, the bio-based polycarboxylic acid plasticizer is obtained by using glycerol and succinic anhydride derived from biomass as raw materials, synthesizing bio-based polycarboxylic acid through esterification reaction, and then performing a ring-opening reaction with hydrophobic epoxy soybean oil, and preparing a bio-based polycarboxylic acid plasticizer with a large molecular weight containing a flexible long carbon chain by controlling different carboxyl / epoxy equivalent ratios (R=0.4). The bio-based polycarboxylic acid plasticizer is degradable and has good compatibility with PLA.
[0011] Preferably, the hydrophobic epoxy soybean oil is obtained by: utilizing the difference in solubility of hydrophobic alcohol solvents for different polar components in the epoxy soybean oil, removing the hydrophilic components by solvent extraction to obtain the hydrophobic epoxy soybean oil; the hydrophobic alcohol solvent is one of tert-butyl alcohol, isobutyl alcohol, n-pentanol, sec-pentanol and n-hexanol.
[0012] Preferably, the cellulose grafted polycaprolactone derivative is obtained by adding microcrystalline cellulose, dimethyl sulfoxide and an organic base DBU (1,8-diazabicycloundec-7-ene) into a high-pressure reactor, replacing with CO2, reacting for a certain period of time under a stable state to obtain a clear and transparent cellulose homogeneous solution, using the organic base DBU as an organic catalyst to make the cellulose hydroxyl group as an initiator to react with Ɛ-caprolactone to form a ring-opening polymerization, thereby synthesizing a cellulose grafted polycaprolactone derivative.
[0013] Preferably, the modified castor oil is obtained by first subjecting sebacic acid and castor oil to an esterification reaction in a flask, with the main ratio of carboxyl groups to hydroxyl groups being 1:1.5, to obtain the modified castor oil.
[0014] Preferably, the degradation rate is controlled by setting a photosensitizer gradient or a surface contact area in the raw material components; the body of the degradable medicinal plastic bottle gradually turns brown with light exposure, because silver nitrate turns brown under ultraviolet light or sunlight; It is explained that by designing the first layer of the surface into a microporous structure, the contact area between the photosensitizer and light is increased; by increasing the amount of photosensitizer used, the degradation rate is increased.
[0015] In a second aspect, the present invention provides a method for preparing a degradable medicinal plastic bottle, comprising the following steps: Step 1, weigh the raw material components according to the mass ratio of polylactic acid, biodegradable elastomer, compound plasticizer, nucleating agent and photosensitizer of 100: (15-20): (2-4): (2-4): (1-3); Step 2: using a high-speed mixer to fully mix the raw material components to obtain a resin mixture; Step 3, melting the resin mixture at 100-400° C., and obtaining a composite resin material through extrusion molding; Step 4: Blow-molding the combined resin material at 190-215° C. to obtain a degradable medicinal plastic bottle.
[0016] (III) Beneficial effects The present invention provides a degradable medicinal plastic bottle and a preparation method thereof, which have the following beneficial effects: (1) The degradable medicinal plastic bottle provided by the present invention is prepared by mixing a biodegradable elastomer, a compound plasticizer, a nucleating agent, a photosensitizer and polylactic acid, adding the mixture into a twin-screw extruder, and extruding and granulating the mixture after melt blending to obtain a modified polylactic acid degradable composite material, which enhances the mechanical properties and crystallization properties of polylactic acid, reduces the water vapor permeability, and improves the toughness of polylactic acid. Ag3PO4 is loaded on titanium dioxide to broaden the spectral response range of the modified polylactic acid degradable composite material, improve the light absorption capacity, reduce the recombination probability of electron-hole pairs, and improve the photocatalytic efficiency. At the same time, Ag3PO4 is a substance with antibacterial properties. When used in medicinal plastic bottles, it can reduce the growth and reproduction of bacteria, thereby keeping the medicines clean and hygienic, and effectively solves the problem of insufficient physical properties, photocatalytic efficiency and antibacterial properties of plastic bottles in the prior art.
[0017] (2) The biodegradable medicinal plastic bottle provided by the present invention controls the degradation rate by setting the photosensitizer gradient or the surface contact area in the raw material components; as the body of the biodegradable medicinal plastic bottle is exposed to light, it gradually turns brown, which helps to control the degradation rate of the plastic bottle and indicate the degradation rate of the plastic bottle.
[0018] (3) The degradable medical plastic bottle provided by the present invention has improved tensile properties, flexibility and fracture strength by compounding plasticizers. Among them, the bio-based polycarboxylic acid plasticizer reduces the glass transition temperature of polylactic acid, the cellulose grafted polycaprolactone derivative enhances the compatibility of polylactic acid, and the modified castor oil improves the flexibility and impact resistance of polylactic acid. The components work together to significantly improve the flexibility and multiple mechanical properties of polylactic acid. DETAILED DESCRIPTION
[0019] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0020] Preparation Examples A1-A4 are used to prepare a biodegradable elastomer, a compound plasticizer, a nucleating agent, and a photosensitizer, including: Preparation Example A1: The biodegradable elastomer is obtained by mixing polyhydroxybutyrate, polycaprolactone, and polybutylene succinate in equal weight ratios.
[0021] Preparation Example A2: The composite plasticizer is obtained by mixing a bio-based polycarboxylic acid plasticizer, a cellulose-grafted polycaprolactone derivative, modified castor oil, and acetyl tributyl citrate in a ratio of 2:2:1:1; The bio-based polycarboxylic acid plasticizer is obtained by: using glycerol and succinic anhydride derived from biomass as raw materials, synthesizing bio-based polycarboxylic acid through esterification reaction, and then reacting with hydrophobic epoxy soybean oil for ring-opening reaction, and preparing a bio-based polycarboxylic acid plasticizer with a large molecular weight containing a flexible long carbon chain by controlling different carboxyl / epoxy equivalent ratios (R=0.4). The bio-based polycarboxylic acid plasticizer is degradable and has good compatibility with PLA. The hydrophobic epoxy soybean oil is obtained by: utilizing the difference in solubility of hydrophobic alcohol solvents for different polar components in epoxy soybean oil, removing the hydrophilic components through solvent extraction to obtain the hydrophobic epoxy soybean oil. The hydrophobic alcohol solvent is one of tert-butyl alcohol, isobutyl alcohol, n-pentanol, sec-pentanol and n-hexanol. The cellulose grafted polycaprolactone derivative is obtained by adding microcrystalline cellulose, dimethyl sulfoxide and organic base DBU into a high-pressure reactor, replacing with CO2, reacting for a certain period of time in a stable state to obtain a clear and transparent cellulose homogeneous solution, using the organic base DBU as an organic catalyst to make the cellulose hydroxyl group as an initiator and Ɛ-caprolactone to undergo a ring-opening reaction polymerization, thereby synthesizing the cellulose grafted polycaprolactone derivative; The modified castor oil is obtained by: firstly performing an esterification reaction between sebacic acid and castor oil in a flask, wherein the main ratio of carboxyl group to hydroxyl group is 1:1.5, and the modified castor oil is obtained.
[0022] Preparation Example A3, the nucleating agent is one of a polylactic acid stereocomplex and TMC-200, wherein the process of obtaining the polylactic acid stereocomplex includes the following steps: melting left-handed polylactic acid, right-handed polylactic acid and polyethylene glycol at 200°C, and processing through a twin-screw extruder or an internal mixer to obtain a polylactic acid stereocomplex.
[0023] Preparation Example A4, the photosensitizer is modified titanium dioxide, and the process of obtaining the modified titanium dioxide includes the following steps: Step S11, weigh a certain amount of loose dry kapok, and soak it in an absolute ethanol solution of TBOT at room temperature, let it stand for 24 hours, then take it out and place it in the air for hydrolysis for 2 hours; Step S12: After the hydrolysis is completed, the kapok is placed in a drying furnace and dried and calcined at 50° C., and the tubular TiO2 is collected for later use; Step S13, under magnetic stirring, add 0.1 g of AgNO3 to 50 mL of an aqueous solution containing 0.5 g of PVP, stir for 30 min, disperse 200 mg of tubular TiO2 in the solution, stir again for 30 min, slowly drop 5 mL of 0.1 mol NaHPO4 into the solution, and let stand for 4 h after ultrasonic stirring; Step S14, collecting the precipitate by centrifugation, washing twice with deionized water and anhydrous ethanol, and then placing the sample in a drying oven and drying it at 50° C. for 6 h to obtain a 1:2 Ag3PO4 / TiO2 composite material; Step S15, surface modification of the collected Ag3PO4 / TiO2 composite material is performed by using a silane coupling agent to improve the stability of the Ag3PO4 / TiO2 composite material and improve its light absorption performance and photocatalytic activity; Step S16, drying in a drying oven at 60°C for 24 hours. In order to improve the crystallinity of the Ag3PO4 / TiO2 composite material nanoparticles, the Ag3PO4 / TiO2 composite material is annealed in a muffle furnace at 350°C for 2 hours to obtain modified titanium dioxide.
[0024] Preparation Examples B1-B7 are used to prepare degradable medical plastic bottles; Preparation Example B1: Test product 1 is obtained by the following preparation process; the preparation process of the degradable medicinal plastic bottle includes the following steps: Step 1, weighing raw material components according to the mass ratio of polylactic acid, biodegradable elastomer, compound plasticizer, nucleating agent and photosensitizer of 100:15:2:2:2; Step 2: using a high-speed mixer to fully mix the raw material components to obtain a resin mixture; Step 3, melting the resin mixture at 225° C. and extruding to obtain a composite resin material; Step 4: Blow-molding the combined resin material at 190-215° C. to obtain a degradable medicinal plastic bottle.
[0025] It needs to be further explained that the polylactic acid is a mixture of poly L-lactic acid and poly D-lactic acid, and the polylactic acid has a glass transition temperature of 60°C, a melting point of 180°C, a tensile strength of 50-65MPa, an elastic modulus of 2000-3500MPa, an elongation of 6%-10%, and a relative density of 1.24g / cm 3 .
[0026] It needs to be further explained that in Preparation Example B1, the biodegradable elastomer is obtained by mixing polyhydroxybutyrate, polycaprolactone, polybutylene succinate and the like in a weight ratio; the compound plasticizer is obtained by mixing a bio-based polycarboxylic acid plasticizer, a cellulose-grafted polycaprolactone derivative, modified castor oil, and acetyl tributyl citrate in a ratio of 2:2:1:1; the nucleating agent is TMC-200; and the photosensitizer is modified titanium dioxide.
[0027] Preparation Example B2: Test product 2 is obtained by the following preparation process; the preparation process of the degradable medicinal plastic bottle includes the following steps: Step 1, weighing raw material components according to the mass ratio of polylactic acid, biodegradable elastomer, compound plasticizer, nucleating agent and photosensitizer of 100:18:3:2:2; Step 2: using a high-speed mixer to fully mix the raw material components to obtain a resin mixture; Step 3, melting the resin mixture at 225° C. and extruding to obtain a composite resin material; Step 4: Blow-molding the combined resin material at 190-215° C. to obtain a degradable medicinal plastic bottle.
[0028] It needs to be further explained that in Preparation Example B1, the biodegradable elastomer is obtained by mixing polyhydroxybutyrate, polycaprolactone, polybutylene succinate and other ingredients in a weight ratio; the compound plasticizer is obtained by mixing a bio-based polycarboxylic acid plasticizer, a cellulose-grafted polycaprolactone derivative, modified castor oil, and acetyl tributyl citrate in a ratio of 2:2:1:1; the nucleating agent is a polylactic acid stereocomplex; and the photosensitizer is modified titanium dioxide.
[0029] Preparation Example B3: Test product 3 is obtained by the following preparation process; the preparation process of the degradable medicinal plastic bottle includes the following steps: Step 1, weighing raw material components according to the mass ratio of polylactic acid, biodegradable elastomer, compound plasticizer, nucleating agent and photosensitizer of 100:20:2:4:1; Step 2: using a high-speed mixer to fully mix the raw material components to obtain a resin mixture; Step 3, melting the resin mixture at 225° C. and extruding to obtain a composite resin material; Step 4: Blow-molding the combined resin material at 190-215° C. to obtain a degradable medicinal plastic bottle.
[0030] It needs to be further explained that in Preparation Example B3, the biodegradable elastomer is obtained by mixing polyhydroxybutyrate, polycaprolactone, polybutylene succinate and other ingredients in a weight ratio; the compound plasticizer is obtained by mixing a bio-based polycarboxylic acid plasticizer, a cellulose-grafted polycaprolactone derivative, modified castor oil, and acetyl tributyl citrate in a ratio of 2:2:1:1; the nucleating agent is TMC-200; and the photosensitizer is modified titanium dioxide.
[0031] Preparation Example B4, test product 4 was obtained by the following preparation process; the difference from Preparation Example B3 is that the raw material components were weighed according to the mass ratio of polylactic acid, biodegradable elastomer, compound plasticizer, nucleating agent, and photosensitizer of 100:20:2:4:2.
[0032] Preparation Example B5, test product 5 was obtained by the following preparation process; the difference from Preparation Example B3 is that the raw material components are weighed according to the mass ratio of polylactic acid, biodegradable elastomer, compound plasticizer, nucleating agent, and photosensitizer of 100:20:2:4:3.
[0033] Preparation Example B6, test product 6 was obtained by the following preparation process; the difference from Preparation Example B1 is that, The raw material components were weighed according to the mass ratio of polylactic acid, biodegradable elastomer, compound plasticizer, nucleating agent and photosensitizer of 100:18:2:2:1.
[0034] Preparation Example B7, test product 7 was obtained by the following preparation process; the difference from Preparation Example B1 is that, The raw material components were weighed according to the mass ratio of polylactic acid, biodegradable elastomer, compound plasticizer, nucleating agent and photosensitizer of 100:20:3:4:2.
[0035] Test case, used to analyze the mechanical properties, degradation properties and water vapor permeability of test products 1-7 and control groups 1-3; The difference between the control group 1 and the test product 1 is that the plasticizer is different; the preparation method of the control group 1 is: polylactic acid, biodegradable elastomer, plasticizer, nucleating agent, and photosensitizer are blended in a ratio of 100:15:2:2:2; the raw material components are evenly mixed and added into a twin-screw extruder, and the control group 1 is prepared by melt blending and blow molding; Further, the plasticizer is epoxidized soybean oil; The difference between the control group 2 and the test product 1 is that the photosensitizer is different; the preparation method of the control group 2 is: polylactic acid, biodegradable elastomer, compound plasticizer, nucleating agent, and photosensitizer are blended in a ratio of 100:15:2:2:2; the raw material components are mixed evenly and then added into a twin-screw extruder, and the control group 2 is prepared by melt blending and blow molding; Furthermore, the photosensitizer is titanium dioxide nanoparticles; Control group 3 is a polylactic acid degradable plastic bottle, which is prepared by obtaining a polylactic acid raw material through a lactide ring-opening polymerization method, heating the polylactic acid raw material to a molten state, and blowing the molten polylactic acid through a mold into a plastic bottle with a specific shape.
[0036] Test method Mechanical properties test: A universal testing machine was used to perform mechanical properties tests to evaluate the mechanical properties and stability of the samples. The tensile modulus, tensile strength, flexural modulus, and flexural strength were obtained by averaging multiple times. The mechanical properties parameters are shown in Table 1. It was found that the test samples 1-7 had good mechanical properties compared with the control group 3. Weathering test: Test products 1-7 and control groups 1-3 were placed in UV-visible light aging test chambers, and their appearance, color, and hardness changes were measured regularly. The hardness loss rates of test products 1-7 after 15 days of UV irradiation at an intensity of 3000uW / cm were 8.9%, 9.1%, 9.5%, 10.3%, 11.8%, 9.4%, and 10.1%, respectively; the degradation rates of test products 3-5 increased, and the colors of the test products changed as the degradation progressed; the hardness loss rates of control groups 1-3 were 9.6%, 7.2%, and 10.7%, respectively; Water vapor transmission rate test: measured at a temperature of 25°C ± 2°C and a relative humidity of 95% ± 5%, the water vapor transmission rates of test products 1-7 were 37.5 mg / (24h·L), 43.0 mg / (24h·L), 43.8 mg / (24h·L), 43.4 mg / (24h·L), 43.4 mg / (24h·L), 49.5 mg / (24h·L), 53.3 mg / (24h·L), and the average water vapor transmission rate was 43.4 mg / (24h·L); Table 1 Mechanical properties parameters
[0037] Summary: The degradable pharmaceutical plastic bottle provided by the present invention has excellent mechanical properties, moderate degradation performance, good water vapor barrier properties and environmental protection, which makes the material have broad application prospects and market potential in the field of pharmaceutical packaging.
[0038] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A degradable medical plastic bottle, the raw material components include polylactic acid, biodegradable elastomer, compound plasticizer, nucleating agent, photosensitizer, characterized in that: The mass ratio of polylactic acid, biodegradable elastomer, compound plasticizer, nucleating agent and photosensitizer is 100: (15-20): (2-4): (2-4): (1-3); The biodegradable elastomer is obtained by mixing polyhydroxybutyrate, polycaprolactone, polybutylene succinate and the like in a weight ratio; the compound plasticizer is obtained by mixing a bio-based polycarboxylic acid plasticizer, a cellulose-grafted polycaprolactone derivative, modified castor oil, and acetyl tributyl citrate; the nucleating agent is one of a polylactic acid stereocomplex and TMC-200; the photosensitizer is modified titanium dioxide; The raw material components are mixed evenly and then added into a twin-screw extruder, and a degradable medicinal plastic bottle is prepared through melt blending and blow molding.
2. A degradable medicinal plastic bottle according to claim 1, characterized in that: The average water vapor permeability of biodegradable medical plastic bottles is 43.4 mg / (24h·L).
3. A degradable medicinal plastic bottle according to claim 1, characterized in that: The modified titanium dioxide is obtained by: Step S11, weigh a certain amount of loose dry kapok, and soak it in an absolute ethanol solution of TBOT at room temperature, let it stand for 24 hours, then take it out and place it in the air for hydrolysis for 2 hours; Step S12: After the hydrolysis is completed, the kapok is placed in a drying furnace and dried and calcined at 50° C., and the tubular TiO2 is collected for later use; Step S13, under magnetic stirring, add 0.1 g of AgNO3 to 50 mL of an aqueous solution containing 0.5 g of PVP, stir for 30 min, disperse 200 mg of tubular TiO2 in the solution, stir again for 30 min, slowly drop 5 mL of 0.1 mol NaHPO4 into the solution, and let stand for 4 h after ultrasonic stirring; Step S14, collecting the precipitate by centrifugation, washing twice with deionized water and anhydrous ethanol, and then placing the sample in a drying oven and drying it at 50° C. for 6 h to obtain a 1:2 Ag3PO4 / TiO2 composite material; Step S15, surface modification of the collected Ag3PO4 / TiO2 composite material is performed by using a silane coupling agent to improve the stability of the Ag3PO4 / TiO2 composite material and improve its light absorption performance and photocatalytic activity; Step S16, drying in a drying oven at 60°C for 24 hours. In order to improve the crystallinity of the Ag3PO4 / TiO2 composite material nanoparticles, the Ag3PO4 / TiO2 composite material is annealed in a muffle furnace at 350°C for 2 hours to obtain modified titanium dioxide.
4. A degradable medicinal plastic bottle according to claim 1, characterized in that: The composite plasticizer is obtained by mixing a bio-based polycarboxylic acid plasticizer, a cellulose-grafted polycaprolactone derivative, modified castor oil, and acetyl tributyl citrate in a ratio of 2:2:1:1, based on mass fraction.
5. A degradable medicinal plastic bottle according to claim 4, characterized in that: The bio-based polycarboxylic acid plasticizer is obtained by using glycerol and succinic anhydride derived from biomass as raw materials, synthesizing bio-based polycarboxylic acid through esterification reaction, and then undergoing a ring-opening reaction with hydrophobic epoxy soybean oil. By controlling different carboxyl / epoxy equivalent ratios (R=0.4), a high molecular weight bio-based polycarboxylic acid plasticizer containing a flexible long carbon chain is prepared. The bio-based polycarboxylic acid plasticizer is degradable and has good compatibility with PLA.
6. A degradable medicinal plastic bottle according to claim 5, characterized in that: The hydrophobic epoxy soybean oil is obtained by: utilizing the difference in solubility of hydrophobic alcohol solvents for different polar components in the epoxy soybean oil, removing the hydrophilic components by solvent extraction, and obtaining the hydrophobic epoxy soybean oil; the hydrophobic alcohol solvent is one of tert-butyl alcohol, isobutyl alcohol, n-pentanol, sec-pentanol and n-hexanol.
7. The degradable plastic bottle for medicine according to claim 3, characterized in that: The cellulose grafted polycaprolactone derivative is obtained by adding microcrystalline cellulose, dimethyl sulfoxide and organic base DBU into a high-pressure reactor, replacing with CO2, reacting for a certain period of time under a stable state to obtain a clear and transparent cellulose homogeneous solution, using the organic base DBU as an organic catalyst to make the cellulose hydroxyl group as an initiator to react with Ɛ-caprolactone for ring-opening polymerization, thereby synthesizing the cellulose grafted polycaprolactone derivative.
8. The degradable plastic bottle for medicine according to claim 3, characterized in that: The modified castor oil is obtained by: conducting an esterification reaction between sebacic acid and castor oil in a flask, with the main ratio of carboxyl group to hydroxyl group being 1:1.5, to obtain the modified castor oil.
9. The degradable plastic bottle for medicine according to claim 1, characterized in that: The degradation rate can be controlled by setting the photosensitizer gradient in the raw material components or the surface contact area.
10. A method for preparing a degradable medicinal plastic bottle, characterized in that: The following steps are involved: Step 1, weigh the raw material components according to the mass ratio of polylactic acid, biodegradable elastomer, compound plasticizer, nucleating agent and photosensitizer of 100: (15-20): (2-4): (2-4): (1-3); Step 2: using a high-speed mixer to fully mix the raw material components to obtain a resin mixture; Step 3, melting the resin mixture at 225° C. and extruding to obtain a composite resin material; Step 4: Blow-molding the combined resin material at 190-215° C. to obtain a degradable medicinal plastic bottle.
Citation Information
Patent Citations
Low-cost degradable plastic bottle and preparation method thereof
CN116041923A
Degradable plastic medicine bottle and preparation method thereof
CN118791852A